Lemanual
  • Lemanual
Help me please A. Given the equation 5x − 4 = −2(3x + 2), solve for the variable. Explain each step and justify your process. B. Megan solved a similar equation below. Is Megan's solution correct? Explain why or why not. 3(2x − 4) = 5x − 1 6x − 12 = 5x − 1 11x − 12 = −1 11x = 11 x = 11 (10 points)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
jjwalton04
  • jjwalton04
Hold on
Lemanual
  • Lemanual
Ok
jjwalton04
  • jjwalton04
for A Let's solve your equation step-by-step. 5x−4=−2(3x+2) Step 1: Simplify both sides of the equation. 5x−4=−2(3x+2) Simplify: (Hide steps) Let's simplify step-by-step. 5x−4=−2(3x+2) 5x+−4=(−2)(3x)+(−2)(2)(Distribute) 5x+−4=−6x+−4 5x−4=−6x−4 Step 2: Add 6x to both sides. 5x−4+6x=−6x−4+6x 11x−4=−4 Step 3: Add 4 to both sides. 11x−4+4=−4+4 11x=0 Step 4: Divide both sides by 11. 11x/11 = 0 11 x=0 Answer: x=0

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

jjwalton04
  • jjwalton04
Shes right Let's solve your equation step-by-step. 3(2x−4)=5x−1 Step 1: Simplify both sides of the equation. 3(2x−4)=5x−1 Simplify: (Hide steps) Let's simplify step-by-step. 3(2x−4)=5x−1 (3)(2x)+(3)(−4)=5x+−1(Distribute) 6x+−12=5x+−1 6x−12=5x−1 Step 2: Subtract 5x from both sides. 6x−12−5x=5x−1−5x x−12=−1 Step 3: Add 12 to both sides. x−12+12=−1+12 x=11 Answer: x=11
Lemanual
  • Lemanual
Thanks guys I wish I can Best response both of you
jjwalton04
  • jjwalton04
But carly her answer came out correct
Lemanual
  • Lemanual
Ok thanks again
carlyleukhardt
  • carlyleukhardt
Ok....Sorry
Lemanual
  • Lemanual
Sorry for what?
carlyleukhardt
  • carlyleukhardt
For being wrong it looked like she was wrong to me
jjwalton04
  • jjwalton04
i just explained it. lol but you tried. After all im not a robot, i might be wrong
Lemanual
  • Lemanual
Oh so megan is right
jjwalton04
  • jjwalton04
Hehe a doggy xD
carlyleukhardt
  • carlyleukhardt
I don't think so but he explained it better
Lemanual
  • Lemanual
Ok
Lemanual
  • Lemanual
Yes, the way she got the answer was wrong, even though she got the right answer.

Looking for something else?

Not the answer you are looking for? Search for more explanations.